HUBUNGAN DISFAGIA DAN PENURUNAN KESADARAN TERHADAP PNEUMONIA ASPIRASI PADA PASIEN STROKE RS ATMA JAYA - Michael Nathaniel Budiarso; Linda Suryakusuma; Luse Luse; Vetinly Vetinly (PERDOSNI, 2018)
THE CORRELATION BETWEEN DISHAGIA AND ALTERED LEVEL OF CONSCIOUSNESS WITH ASPIRATION PNEUMONIA IN STROKE PATIENTS AT ATMA JAYA HOSPITALABSTRACTIntroduction: Approximately 40-96% of stroke patients will develop complications; the most frequent is pneumonia (33%). This is due to the underlying clinical manifestation of stroke such as dysphagia, immobilization, altered level of consciousness, and immune suppression which increases the risk of aspiration, therefore increases the risk for aspiration pneumonia. Early detection of aspiration pneumonia and its risk factors in stroke patients are essential, but the number of researches regarding this in Indonesia is still limited.Aims: To study the correlation between dysphagia and altered level of consciousness in stroke patients with aspiration pneumonia in Atma Jaya Hospital, Jakarta.Methods: This is a retrospective cohort research with a cross sectional approach towards 263 stroke patients in Atma Jaya Hospital, February 2016 until October 2017. Data was taken from the stroke registry and medical records, and analized with Chi-square test (α=0.05).Results: The incidence for aspiration pneumonia was 16% in the study population, most of which being male (57.8%), age <65 years old (79.5%), and length of education <9 years (71.5%). Age >65, dysphagia and altered level of consciousness were statistically significant with Odds ratio (OR) 2.26, 3.92, and 8.67, respectively.Discussion: Male, age <65 years old, and length of education <9 years were correlated with poor daily life habits which increases the risk of getting a stroke. Age >65 years old, dysphagia and altered level of consciousness can disturb the coordination and swallowing reflex which makes patients more vulnerable to aspiration and develop aspiration pneumonia.Keywords: Altered level of consciousness, aspiration pneumonia, dysphagia, strokeABSTRAKPendahuluan: Sebanyak 40-96% pasien stroke akan mengalami komplikasi, terutama pneumonia (33%). Hal ini dimungkinkan oleh adanya kecenderungan disfagia, imobilitas, penurunan kesadaran, dan supresi imunitas yang mempermudah terjadinya aspirasi hingga terjadi pneumonia aspirasi. Deteksi awal faktor risiko pneumonia aspirasi pada pasien stroke sangat penting, namun penelitiannya masih terbatas di Indonesia.Tujuan: Mengetahui hubungan antara disfagia dan penurunan kesadaran terhadap kejadian pneumonia aspirasi pada pasien stroke di RS Atma Jaya, Jakarta.Metode: Penelitian kohort retrospektif dengan pendekatan potong lintang terhadap 263 pasien stroke di RS Atma Jaya. Penelitian dilakukan mulai Februari 2016-Oktober 2017. Data diperoleh melalui data register stroke dan rekam medis. Analisis dilakukan menggunakan uji Chi-square dengan nilai α=0,05.Hasil: Insiden pneumonia aspirasi pada pasien stroke adalah 16%. Didapatkan mayoritas populasi laki-laki (57,8%) berusia <65 tahun (79,5%), dan berpendidikan <9 tahun (71,5%). Usia >65 tahun, disfagia, dan penurunan kesadaran memiliki hubungan yang bermakna secara statistik terhadap kejadian pneumonia aspirasi dengan rasio Odds (RO) 2,26, 3,92, dan 8,67 kali lipat.Diskusi: Laki-laki, usia <65 tahun, dan pendidikan <9 tahun berkaitan dengan pola kesehatan hidup buruk yang meningkatkan faktor risiko terjadinya stroke. Usia >65 tahun, disfagia, dan penurunan kesadaran dapat mengganggu koordinasi dan refleks menelan, sehingga pasien stroke lebih rentan terjadi aspirasi dan mengalami pneumonia aspirasi.Kata kunci: Disfagia, penurunan kesadaran, pneumonia aspirasi, stroke